Correlation Analysis between Color Parameters and Sensory Characteristics of Rice with Different Milling Degrees. Issue 4 (20th October 2013) - Zhong, Yejun; Liu, Wei; Xu, Xingfeng; Liu, Chengmei; Tu, Zongcai
Abstract The effects of degrees of milling on color parameters and sensory characteristics of rice were evaluated, and their relationships were established by the method of Pearson correlation analysis and regression analysis. Results showed that with the increase of milling degree, color value a* and b* gradually decreased while L* value and eating quality correspondingly increased. The correlation analysis revealed that sensory characteristics were significantly negatively correlated with a* and b* value, and significantly positively correlated with L* value. In terms of color parameters, L* value had a significant negative correlation with a* and b* value, while a* and b* values were significantly positively correlated. Eating quality showed a linear relationship with a*, b* and L* value, and the R2 values for the relationship were in the range of 0.90–0.99. Regression equations had high R2 values and could be used to predict the eating quality of cooked rice. Practical Applications The traditional method of judging sensory characteristics of rice, which mainly conducted by experienced inspector, needs plenty of people and time for measurement. New measurement system, based on the establishment of relationship between color parameters and sensory characteristics, assists in quick locating the optimum degrees of milling to prevent poor judgment and increasing the accuracy and efficiency of working, meanwhile helps to predict the eating quality of cooked rice.